Interactions between Pythium tracheiphilum, Meloidogyne hapla and Pratylenchus penetrans on lettuce - Gracia, J.A.; Reeleder, R.D.; Bélair, G. (Phytoprotection, 1991)
The growth of lettuce plants (Lactuca sativa) was reduced by Pythium tracheiphilum, Meloidogyne hapla and Pratylenchus penetrans under growth chamber conditions. A marked additive decrease in lettuce growth was observed when P. tracheiphilum and M. hapla were added to the soil simultaneously. Interactions between P. penetrans and P. tracheiphilum, however, were additive at low populations of F. tracheiphilum, but appeared to be negative at high populations of the fungus. The fungus had a negative effect on the populations of both species of nematode in roots.